2014
DOI: 10.1016/j.ijsu.2014.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Does helicobacter pylori infection have influence on outcome of laparoscopic sleeve gastrectomy for morbid obesity?

Abstract: HP infection seems not to influence postoperative outcome of patients operated of laparoscopic sleeve gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…Albawardi et al further corroborated our findings, and their work was less susceptible to type two error due to a higher leak rate of 5.6 % [4]. To the authors' knowledge, all reported series have reported no increased risk of surgical complications following sleeve gastrectomy when H. pylori infection is present in the surgical specimen [4,6,10,11].…”
Section: Discussionsupporting
confidence: 84%
“…Albawardi et al further corroborated our findings, and their work was less susceptible to type two error due to a higher leak rate of 5.6 % [4]. To the authors' knowledge, all reported series have reported no increased risk of surgical complications following sleeve gastrectomy when H. pylori infection is present in the surgical specimen [4,6,10,11].…”
Section: Discussionsupporting
confidence: 84%
“…Some findings may vary according to geographic distributions. For example, the frequency of HP infections can vary from 3.2% to 64% (15)(16)(17)(18)(19)10,(20)(21)(22)(23). This rate was 35% in our series.…”
Section: Discussionmentioning
confidence: 47%
“…[14] Another challenge in the case of restoring bariatric procedures will be the need to observe whether the SARS-CoV-2 infection affects the longterm effects of surgical treatment. Similar studies have so far been designed for other types of infections [15].…”
Section: Discussionmentioning
confidence: 94%